The impact of childhood obesity on human capital in high-income countries: A systematic review - Segal,AB; Huerta,MC; Aurino,E; Sassi,F (Obesity Reviews, 2021)
Current evidence of the impact of childhood obesity on human capital development does not point in a consistent direction, and its interpretation is challenging. We carried out a systematic review of studies from highincome countries that used robust causal inference approaches to assess the impact of childhood overweight and obesity on outcomes typically linked to human capital development in economics. Global Health, Medline and EconLit were used to search for peerreviewed papers. Three reviewers independently assessed study quality using the NewcastleOttawa Scale. Nineteen papers representing 22 studies met the inclusion criteria. Included studies were categorized based on three components of human capital: cognitive performance (n = 18), measured through test scores; educational attainment (n = 3), through grade progression and college completion; and labour market outcomes (n = 1), through wages. We find that childhood overweight and obesity hinder education outcomes, with effects mostly observed at older ages of exposure measurement (12+ years). Girls with overweight and obesity experienced larger negative effects and more often than boys. Future research should elucidate the pathways through which childhood obesity impacts human capital development, to support policies that may mitigate those impacts, thus averting social costs that are currently widespread, increasing and unaccounted for.